Education and Inclusion: equity and learning as capital strategies - Rosalba Maria Cardoso Garcia; Maria Helena Michels (Universidade Federal do Rio Grande do Sul, 2022)
In this article, international educational policy guidelines between 1990 and 2020 were discussed, and three generations of special education policies in Brazil were analyzed, relating education and inclusion with equity and learning strategies. Such strategies are related to educational diversification, curriculum flexibility, differentiation of trajectories, and skills and competencies that do not require school institutions and knowledge. There is a multifaceted perspective related to inclusion, combining segregated and integrationist services. The proposals under discussion lead to lower education levels and de-schooling processes, reinforcing the inequality mechanisms that constitute capital sociability.